PREFABRICATED BUILDING OF PANEL STRUCTURE AT SYOWA STATION - Fumio TSUCHIYA (Antarctic Record, 1966)
A prefabricated building was designed in 1965 by the Committee for Antarctic Buildings and built in 1966 at Syowa Station. This building is of box-frame structure, which can be easily assembled in short time for multi-purpose establishment in the Antarctic area, such as sleeping quarters, mess hut, laboratory, etc. Therefore, even expedition members without any experiences in such construction are able to put it together. With the said building, thickness of the panel and its weight are exceptionally much more than those of the standard type, since the building is expected to accommodate deep frozen food as a cold storage. Of course, there is no changes in basic design. The outline of this building for cold storage is as follows : [table] Each panel contains insulation material of 100mm thick which is sandwiched by water-proof plywood. Exterior surface of the panel is covered with stainless steel sheet and in-terior is lined with vinyl resin coated steel sheet. This prefabricated building has the following features : 1. For the jointed part of each corner of the structure, the unique prefabricated Lshaped corner-wall is employed. Since it is manufactured under a standard size, other components of the establishment, such as roof, floor, and side-wall can also be standardized. Besides, such tightly fastened prefabricated corner completely eliminates the fundamental weakpoint that has been unavoidable so far withstanding shock and tortion. 2. As for the jointing method of two panels, a long sized bolt of 13φ is tightly screwed across the both adjacent frames, thus the surface of the both frames being tightly put together each other. In this method, only the bolting at two points in a panel substitutes for the traditional connecting method that is less endurable against shock and tortion. 3. Each jointed surface of the panel is finished with foamed chloroprene rubber, so that the gaps at the jointed surface can be completely eliminated. This foamed rubber lining has another merit that the elasticity of the rubber makes the errors characteristic to the assembly of the customary prefabricated structure practically ignorable.